Borges: el Otro Arabesk. Case Study: The Aleph - Yasser Sedrati; Walid Djari (Литература двух Америк)
This paper will address the question of the Borgesian approach towards writing multilayered philosophical fiction. It will attempt to stratify his artistic prescription towards constructing deep philosophical testimonies which amalgamate different historical and fictional narratives. The latter will be thoroughly examined in his oeuvres which introduced Islamic heritage specifically, wherein the researchers argue that the fascination which Islam seems to exert on Borges, écrivain préféré of Derrida is far less concerned with remote isolated small desert villages, minarets, raging sultans, swords, harems of T.E. Lawrence and Richard Burton and so on. It is rather drawn on more advanced methods of intellectual anatomy that cites supposed informants who are knowledgeable enough to define figures like Omar El-Khayyam, Averroes, Ibn-Khaldun, and El-Baladhouri. The findings show that the authority is often authorial, and sometimes dependent on complex narratological weaves in addition to standard Orientalist package.